106 Effects of Revalor-XH and combination Revalor-IH/Revalor-200 on Yearling Heifer Growth Performance and Carcass Characteristics. (30th November 2020) - Carlson, Zachary; Erickson, Galen E; Dicke, Bill; Streeter, Marshall
Abstract: A commercial feedlot trial utilizing 870 crossbred heifers (initial BW = 322; SD = 9 kg) examined two implant strategies on growth performance and carcass characteristics. Treatments included: 1) Revalor-IH on d 1 (80 mg trenbalone acetate (TBA)/8 mg estradiol (E2), noncoated) and re-implanted with Revalor-200 on d 101 (200 mg TBA/20 mg E2, noncoated (REV-IH/200); or 2) Revalor-XH on d 1 (200 mg TBA/20 mg E2, partially coated (REV-XH). There were no differences (P > 0.23) observed for live performance including final BW, DMI, ADG, and feed efficiency between implant treatments. There were no differences (P ≥ 0.17) in carcass-adjusted final BW or ADG between implant strategies. There were no differences (P ≥ 0.28) observed for DMI before or after re-implanting for heifers given REV-IH/200 compared to heifers given REV-XH. Heifers implanted with REV-IH/200 had greater carcass-adjusted feed efficiency compared to REV-XH (0.156 vs. 152; P = 0.03). Heifers implanted with REV-IH/200 had larger LM area compared to heifers with REV-XH (88.4 vs. 83.9 cm 2 ; P < 0.01). Calculated yield grade was lower for heifers implanted with REV-IH/200 compared to heifers implanted with REV-XH (3.75 vs. 3.89; P < 0.01). Hot carcass weights, dressing percent, marbling, and 12 th rib back fat were not different (P ≥ 0.11) among treatments. Heifers implanted with REV-IH/200 had a shift towards lower USDA yield grade distribution compared to REV-XH implanted heifers (P = 0.05). The REV-IH/200 combination provided 280 mg of TBA and 28 mg E2, while total active ingredient dose for REV-XH was 200 mg TBA and 20 mg E2. Therefore, minimal differences were observed in carcass-adjusted feed efficiency, LM area, and calculated yield grade between REV-IH/200 and the partially coated REV-XH implant.